Impact of Health Literacy on Medication Engagement Among Adults With Diabetes in the United States: A Systematic Review. Issue 4 (August 2020) - Chima, Charles C.; Abdelaziz, Aya; Asuzu, Chisom; Beech, Bettina M.
Purpose: The purpose of this systematic review is to assess evidence of a relationship between health literacy and medication engagement (formerly referred to as medication adherence) among adults with diabetes mellitus in the United States. Methods: Literature searches were conducted in PubMed, Ovid Medline, CINAHL, Embase, PsycInfo, and Scopus from the inception of each database to April 2020. Studies were included if they met all of the following criteria: (1) conducted in the United States, (2) the population of interest was adults ≥18 years with a diagnosis of type 1 or type 2 diabetes, (3) medication engagement was an outcome variable, (4) a direct and not a mediating relationship between health literacy and medication engagement was assessed, (5) a quantifiable measure of association was reported, and (6) a full-text journal article or dissertation was available. Quality of published evidence was graded according to Joanna Briggs Institute Critical Appraisal Checklists appropriate for the respective study designs identified. Results: Thirteen articles from 11 unique studies were retained in the review, most of which used a cross-sectional design. Four out of 11 studies found a direct positive association between health literacy and medication engagement. Two of the 4 studies with positive findings had significant methodological shortcomings. Conclusions: There is some evidence that health literacy is associated with medication engagement among adults with diabetes in the United States. Properly designed and executed longitudinal studies are needed to better elucidate the relationship between health literacy and medication engagement among adults with diabetes.